(untitled) (CIPEEX, 2025)
This study examines the intersection between human rights and religion, focusing on how religious traditions, particularly the Judeo-Christian tradition, influence the understanding and promotion of human rights in contemporary Brazil. Using works by C.S. Lewis, Max Weber, and Vishal Mangalwadi, alongside the Universal Declaration of Human Rights as a reference, the research explores how religious values can either strengthen or challenge the application of human rights principles. The methodology combines bibliographic analysis with insights from interviews with a Doctor of Law specializing in human rights. The results highlight the significant role of religious traditions in shaping moral foundations for human rights, while also revealing tensions between religious freedom and other fundamental rights, such as gender equality and minority protections. The study concludes that constructive dialogue and reform within religious practices are essential to align spiritual principles with universal human rights values, fostering a more just and inclusive society.